Show that line y = 2mx - 1 intersects with the curve y = mx^2 - x + m for all non-zero values of m?
- Illusional SelfLv 61 decade agoBest Answer
Line 1: y = 2mx- 1
Curve 2: y = mx²- x+ m
What happens when both L1 and C2 intersect each other? Their (x,y)-values are the same:
y = y
2m*x- 1 = m*x²- *x+ m <--- (*x) is the value of x at the intersection point
I want to know all about m, so let's try out some algebra to split m apart from the rest.
m*x²- *x+ m = 2m*x- 1
m*x²- 2m*x+ m = *x- 1
m(*x²- 2*x+ 1) = *x- 1
m(*x- 1)² = *x- 1
m = (*x- 1)/(*x- 1)²
Nothing was told about *x not being valid at some specific point, so at first *x is valid whatever values it assumes. But notice that m isn't valid when *x equals 1, because doing so the denominator of m equals zero. Let's see what happens when *x approaches 1:
**limit of m when *x approaches 1 from the right = lim 1/(*x- 1) = 1/0 = +infinite
**limit of m when *x approaches 1 from the left = lim 1/(*x- 1) = -1/0 = -infinite
So the bigger the absolute value we choose for m, the more likely the curves are going to intercept each other only around *x = 1. For every value of m, both L1 and C2 are going to intersect each other at more than one point-- except at m = 0 (see details below).
Since there are no objections against m assuming specific values, ***both curves intersect each other no matter what's the value for "m"***. Even when m equals 0:
Line 1: y = -1
Curve 2: y = -x
Where do both intersect each other? At *x = 1.
- just♪wonderingLv 71 decade ago
In order for the line and curve to intersect, there must be a point or point where:
2mx-1 = mx^2 - x + m
mx^2 - (2m+1)x +(m+1)=0
x = ((2m+1)+/-sqrt(4m^2+4m+1-4m^2-4m)))/2m
x=1 or x = (m+1)/m
for all m not equal to zero.
- Anonymous3 years ago
The function is y = f(x) mean we are in 2d set up. If P and Q are 2 factors on the curve The tangent at P is the restricting posititon of secant PQ as Q has a tendency to P alongside THE CURVE. So first, the question that a secant shifted // to itself does not get up. 2d, secant is a line so we are able to no longer communicate approximately its "length" or a tanget at P to exist, the function would desire to have spinoff defined at P. Geometrically the curve would desire to be mushy. X-axis is in reality tangent to y = x^3 on the muse. The curves like circle and different (mushy) conic sectios supply an effect that the curve would desire to lie completely on a similar edge of the tangent. in spite of the undeniable fact that it no longer so! i think this suffices, Madhukar Sir.
- 1 decade ago
2m is the slope of the line
-1 is the y-intercept
*The line will always pass the point (0,-1)
BAck to (0,-1)
y = mx^2 - x + m will not be a curve anymore but a line...
- How do you think about the answers? You can sign in to vote the answer.
- Anonymous1 decade ago
using the cuadratic formula
we find that:
x must be either
-(2m+1) + sqr ( (2m+1)^2-4m(-m-1) )
-(2m+1) - sqr ( (2m+1)^2-4m(-m-1) )
there are solutions if the radical (whatever is inside the square root) is not cero:
(2m+1)^2-4m(-m-1) =4m^2+4m+1 +4m^2+4m
=8m^2 +8m +1,
now, this is another quadratic equation, or parabola.
to check if this equation is ever negative, there are several things you could do. One of them is to find its roots:
[-8 + sqr(32)]/2
or [-8 - sqr(32)]/2
with the help of a calculator (or however you want), you see that
both are negative numbers, so
for all m>=0 , 8m^2 +8m +1>=1, in particular positive, therefore
the original problem will always have 2 solutions.
please let me know if it is ok, or if somehting is not clearSource(s): h
- Anonymous1 decade ago
Set the two y's equal and solve for x using the quadratic formula.
The results are: x=1 and x=(m+1)/m m cannot be zero. Q.E.D.
- 1 decade ago
Yeah!.... Good luck with that one!